Musical Creation Uma Yuga | Tabuh Kreasi Uma Yuga - Wayan Aldy Arya Hartawan (GHURNITA: Jurnal Seni Karawitan, 2023)
Efforts to protect rice fields from land conversion, sanctity and preservation of Subak as a traditional institution imbued with supporting the existence of Balinese Culture by Hinduism, for community members who desecrate the sanctity of rice fields, will be given appropriate sanctions. The author wants this article to exist in the eyes of people who see rice fields in one eye. A humanist named I Gede Anom Ranuwara emphasized that "Subak Sawah in Balinese is called Carik, which means a point or gecek in Balinese script, which is defined as a point that irresponsible people cannot touch because they have traded land rice fields for investors who will be used as buildings in the form of houses, office buildings. In the creative process of making this work, the stylist found the inherent character of tradition and could be processed by various patterns on the gong kebyar instrument, namely the xylophone pattern. The stylist chose this pattern because it has a high presence among young people who listen to astonishing patterns when processed into arrangements. New. This new renewal is a benchmark with a new culture for the people of Bali; a small example is the rice fields, which are now being renovated into new buildings, which have a hard impact on the broader community.